the Dampak Transformasi Digital terhadap Praktik Akuntansi: Kajian Literatur Sistematis: -- - Endah Arum Wangi (JURNAL RISET AKUNTANSI JAMBI, 2024)
Digital transformation in accounting has brought significant changes in how accountants perform their tasks, particularly in improving the efficiency and accuracy of financial reporting. This study aims to explore the impact of digital technologies such as cloud computing, big data analytics, blockchain, and artificial intelligence on accounting practices. Using a Systematic Literature Review (SLR) methodology, this research analyzes various studies discussing the application of technology in accounting and its effects on accounting performance. The findings indicate that these digital technologies have accelerated data collection and analysis processes, as well as improved the accuracy of financial reports. Cloud computing enables real-time collaboration among accounting teams, while big data analytics provides deeper insights for financial analysis and decision-making. On the other hand, technologies such as blockchain and artificial intelligence offer higher transaction security and improve audit efficiency. However, the adoption of these digital technologies also faces challenges, particularly in terms of the technical skills required by accounting personnel. Therefore, it is crucial for organizations to provide adequate training to fully optimize these technologies. Overall, digital transformation in accounting offers great potential to enhance accounting performance but requires additional efforts in training and technology management.